Effects of Curcumin on Iron Overload in Rats - Gülüzar Özbolat; Arash Alizadeh Yegani (Sudan Journal of Medical Sciences)
Background: Iron overload, common in patients with hematological disorders, is a key target in drug development. This study investigated the effects of curcumin on iron overload in rats.